Evaluasi Kinerja Struktur pada Gedung Eksisting Tujuh Lantai dengan FEMA 310 - Nur Khotimah Handayani (Universitas Teuku Umar, 2021)
FEMA 310 guides in evaluating the performance of existing building structures where the Indonesian code has not provided standard rules for it. FEMA 310 is used to evaluate an existing seven-story building in Barek, Yogyakarta which has limited ductility. FEMA 310 consists of 3 stages, namely Tier 1, Tier 2, and Tier 3. This study is devoted to comparing the evaluation of Tier 2 results (linear static procedures) with Tier 3 results (nonlinear static procedures). The results have shown that the Tier 2 evaluation is well correlated with Tier 3 for the case of a seven-story building with limited ductility. This confirms that Tier 2 evaluations are capable to provide performance evaluations for low-rise to medium-rise buildings with limited ductility capacity.